Natural language processing with Python and spaCy : a practical introduction - Vasiliev, Yuli (No Starch Press, 2020)
"Teaches the foundations of natural language processing (the task of converting human language into data a computer can process), including how to understand a user's intent, customize a statistical model, and set up a basic chatbot"--